PERLINDUNGAN HAK WARGA TERHADAP PENEGAKAN HUKUM DI BIDANG KEHUTANAN - Hakim, Muhammad Zulfan (Universitas Gorontalo, 2018)
AbstractLaw enforcement in environmental law especially in forestry sector has been living in a new era since the birth of some regulations in environemntal law. Since then, sectoral regulations also emerging and of course this regulations need to be uphold, in order to maintain thefunction of our environment. Beside the Law No. 41/1999 about Forestry, there is also Law No. 18/ 2013 about Prevention and Protection From Forest Destruction. In the other hand, this law are conflicting with the natives that already living in forest area, long before that region stated as a protected forest by the government. This paper tries to explain how to handle such confilct between indigenous people that already living in the forest and the law enforcement agent since they have been living their way since long time ago like their anchestors.